We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
33
4
avatar

Hi, can someone help me please with these two questions?

 

 

Same for this question. I'm not good with these kinds of problems so if someone could provide a how-to and the answer :)

 Mar 11, 2019
 #1
avatar+99237 
+1

First one

 

f(2)  = Ln (3*2) + 2.5   =   Ln (6) + 2.5

f(7) = Ln (3*7) + + 2.5  =  Ln ( 21) + 2.5

 

Avg rate of change  from   2 to 7 =

 

[ f(7) - f (2)]          [  (Ln(21 + 2.5) - (Ln(6) + 2.5) ]             Ln(21) - Ln(6)

__________  =   _________________________   =       ___________   ≈  0.25

    7 - 2                                 5                                                   5

 

 

cool cool cool

 Mar 11, 2019
 #2
avatar+99237 
+1

Second one

 

Don't get intimidated, here   !!!

 

f(64) = -∛ 64  =  -4

f(8) =  - ∛ 8   =   -2

 

So

 

Avg rate of change from x = 8 to x = 64   is given by :

 

[ f(64) - f(8)]           -4 - (-2)             -2               -1

_________  =        ______   =       ___    =      ___

      64 - 8                   56                56               28

 

 

 

 

 

cool cool cool

 Mar 11, 2019
 #3
avatar
0

Thanks, CPhill!!! smiley

Guest Mar 11, 2019
 #4
avatar+99237 
0

OK.....!!!

 

cool cool cool

CPhill  Mar 11, 2019

9 Online Users